VALUE OF THE FIRM: INFLATION AND ROLE OF DIVIDEND DECISION MEDIATION - Sumani Sumani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2020)
The objective of this study was to determine the effect of leverage, insider ownership, investment opportunity set (IOS) and inflation on dividend decision. Besides, to prove the effect of leverage, insider ownership, investment opportunity set (IOS) and inflation on firm value through the role of dividend decision mediation and to determine the direct effect of dividend policy on a value of the firm in the consumer goods industry sector. The population is companies in the consumer goods industry sector listed on the IDX during the period 2010-2018. The sampling method uses purposive sampling technique — the total sample of 38 companies using 342-panel data. The analytical method used is path analysis. The results showed that insider ownership and investment opportunity set (IOS) significantly influence dividend decision. However, leverage and inflation do not affect the dividend decision. Also, insider ownership and inflation have a significant effect on the value of the firm, but leverage and investment opportunity sets (IOS) do not affect. Dividend decision affects the value of the firm; besides, dividend decision is proven to significantly play a role in mediating the influence of insider ownership and investment opportunity sets (IOS) on the value of the firm.